2016
DOI: 10.3727/096368915x689794
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Derived Extracellular Matrix Enhances Cardiogenic Properties of Human Cardiac Progenitor Cells

Abstract: The use of biomaterials has been demonstrated as a viable strategy to promote cell survival and cardiac repair. However, limitations on combinational cell-biomaterial therapies exist, as cellular behavior is influenced by the microenvironment and physical characteristics of the material. Among the different scaffolds employed for cardiac tissue engineering, a myocardial matrix hydrogel has been shown to promote cardiogenesis in murine cardiac progenitor cells (mCPCs) in vitro. In this study, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…The general conclusion was that the decellularized material alone was able to guide differentiation and maturation of cells into a cardiac cell fate. This was demonstrated with hESCs, hESC derived cardiomyocytes, human mesendodermal cells, rat cardiac progenitor cells, and neonatal rat ventricular myocytes on entire decellularized hearts, hydrogels, collagen composite hydrogels, and 2D coatings [42, 49, 51, 7274]. One of these studies encapsulated hESC embryoid bodies into hydrogels with varying percentages of porcine heart ECM and observed that the higher percentage of ECM correlated with increased cardiac markers and increased number of contracting cells with larger contraction amplitudes [42].…”
Section: Ecm Effects On Cell Differentiationmentioning
confidence: 99%
“…The general conclusion was that the decellularized material alone was able to guide differentiation and maturation of cells into a cardiac cell fate. This was demonstrated with hESCs, hESC derived cardiomyocytes, human mesendodermal cells, rat cardiac progenitor cells, and neonatal rat ventricular myocytes on entire decellularized hearts, hydrogels, collagen composite hydrogels, and 2D coatings [42, 49, 51, 7274]. One of these studies encapsulated hESC embryoid bodies into hydrogels with varying percentages of porcine heart ECM and observed that the higher percentage of ECM correlated with increased cardiac markers and increased number of contracting cells with larger contraction amplitudes [42].…”
Section: Ecm Effects On Cell Differentiationmentioning
confidence: 99%
“…2,3 Further processing of decellularized ECM into a hydrogel form also allows them to be cast in a variety of 3D shapes for cell culture or injected into host tissue for in situ tissue engineering. 4-8 Stem and progenitor cells seeded on decellularized ECM scaffolds, 9-11 ECM-based coatings, 12,13 and ECM-derived hydrogels 14,15 have been shown to have improved survival, increased proliferation, and differentiate in a tissue-specific manner. Moreover, decellularized ECM and ECM derived hydrogels have been shown to recruit progenitors cells in vivo 16-18 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, dECM exhibits shear thinning behavior upon injection, characterized by a decrease in viscosity upon increases in shear rate, providing a defense layer to injected cells . Numerous studies have shown dECM can be processed into a hydrogel from various tissues, including the heart, pancreas, arteries, brain, lung, meniscus, and dermis . While providing great applicability, dECM hydrogels are characterized by reduced mechanical resilience compared to the native tissue .…”
Section: Decm Processing Approachesmentioning
confidence: 99%
“…Moreover, the dECM hydrogel enables the retention of injected cells and provides them with a bioactive and supporting microenvironment following transplantation, thus promoting their re‐acclimation, leading to fortification and biological regeneration of the ischemic cardiac tissue. Vast research toward the application of dECM‐based hydrogels for cardiac repair, predominantly led by the Christman group, showed that the biological support of dECM hydrogels promotes the proliferation and differentiation of cardiac progenitor cells,and improves infarcted cardiac function (Figure 2h,i) . On the other hand, the mechanical and physical properties of the hydrogels induce endothelial and smooth muscle cell infiltration, as well as arteriole formation .…”
Section: Applications Of Processed Decm‐based Materialsmentioning
confidence: 99%